1992
DOI: 10.1111/j.1528-1157.1992.tb01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Epilepsy in Ulanga, a Rural Tanzanian District: A Community‐Based Study

Abstract: A random cluster sample survey of approximately 18,000 people in 11 villages was performed in Ulanga, a Tanzanian district with a population of approximately 139,000 people. Well-instructed fourth-year medical students and neurologic and psychiatry nurses identified persons with epilepsy using a screening questionnaire and sent them to a neurologist for detailed evaluation. Identified were 207 subjects (88 male, 119 female) with epilepsy; of these, 185 (89.4%) (80 male, 105 female) had active epilepsy. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
115
6
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 17 publications
25
115
6
5
Order By: Relevance
“…Our findings confirm high prevalence rates of epileptic seizures/epilepsy in the hospital and the community, which agrees with the results of previous epidemiological studies of epilepsy in sub-Saharan Africa [5,6,9,[13][14][15][16][17][18][19]. Most studies conducted in parts of Africa and Latin America indicate higher prevalence rates of epilepsy than have been found in high-income countries, but these prevalence rates can vary within a single country, as shown in Benin, the Ivory Coast, Senegal and Tanzania [6,9,19].…”
Section: Prevalence Of Epilepsy In Sub-saharan Africasupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings confirm high prevalence rates of epileptic seizures/epilepsy in the hospital and the community, which agrees with the results of previous epidemiological studies of epilepsy in sub-Saharan Africa [5,6,9,[13][14][15][16][17][18][19]. Most studies conducted in parts of Africa and Latin America indicate higher prevalence rates of epilepsy than have been found in high-income countries, but these prevalence rates can vary within a single country, as shown in Benin, the Ivory Coast, Senegal and Tanzania [6,9,19].…”
Section: Prevalence Of Epilepsy In Sub-saharan Africasupporting
confidence: 82%
“…Most studies conducted in parts of Africa and Latin America indicate higher prevalence rates of epilepsy than have been found in high-income countries, but these prevalence rates can vary within a single country, as shown in Benin, the Ivory Coast, Senegal and Tanzania [6,9,19]. In a recent large-scale study from Kenya, it was shown that the active prevalence was only 4.5/1000, and therefore in the range of prevalence rates of high-income countries, with a high heterogeneity of prevalence rates across different areas ranging from below 1.0/1000 to 12.9/1000 [3].…”
Section: Prevalence Of Epilepsy In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides looking at seizure control and reevaluating the mental status of 260 patients, selected focus-group discussions were held with patient groups and controls, both in the clinic area of Mahenge and in Ruaha, a remote area where no epilepsy clinic has been established (29). The people in both areas belong to the same culturallinguistic group and show an unusual high prevalence of epilepsy (30). Five patient and five control groups of…”
mentioning
confidence: 99%
“…The whole body may lose muscle tone, and the person can suddenly fall. [41][42][43][44][45][46] Tonic or Clonic Seizures: In tonic seizures, the muscles contract and consciousness is altered for about 10 seconds. Clonic seizures, which are very rare, occur primarily in young children, who experience spasms of the muscles but not tonic rigidity.…”
Section: Atonic Seizuresmentioning
confidence: 99%